The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.5271/sjweh.1823
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress and human performance.

Abstract: ENANDER AE, HYGGE S. Thermal stress and human performance. Scand J Work Environ Health 1990;16(suppl 1):44-50. There is evidence that the thermal stress encountered in many work environments may negatively affect various aspects of human performance and behavior. Evaluation of the empirical research is, however, complicated by differences in both the methodology and the definition of the basic stimulus. Effects of heat and cold stress are briefly reviewed, with particular regard to theoretical considerations.K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 40 publications
1
56
1
3
Order By: Relevance
“…A relationship between heat stress and injury occurrence has been reported several times over the last 35 yr [11][12][13][14] . However these studies were conducted in developed non-tropical countries; this leaves unanswered questions about the effect of heat stress on occupational injury in tropical developing countries where temperatures and humidity are already high.…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between heat stress and injury occurrence has been reported several times over the last 35 yr [11][12][13][14] . However these studies were conducted in developed non-tropical countries; this leaves unanswered questions about the effect of heat stress on occupational injury in tropical developing countries where temperatures and humidity are already high.…”
Section: Introductionmentioning
confidence: 99%
“…Manual dexterity is frequently used to evaluate hand function and is important during hand manipulation. Hand/finger skin temperature is considered a vital factor in dexterity (Schiefer et al, 1984;Enander, 1984;Enander & Hygge, 1990;Brajkovic & Ducharme, 2003, Chen et al, 2010 and hand performance (Riley & Cochran, 1984;Havenith et al, 1995, Chen et al, 2010. More importantly, such impairment may lead to an increased number of accidents (Müller, 1982; cited by Havenith et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to cold environments and contact with cold materials have been reported impair tactile sensitivity in the hands (Enander, 1984), hand dexterity (Schiefer et al, 1984;Riley & Cochran, 1984;Enander & Hygge, 1990;Heus et al, 1995), and tracking performance (Goonetilleke & Hoffmann, 2009). Manual dexterity is frequently used to evaluate hand function and is important during hand manipulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that decrease in self-confidence performance and in the capacity of thinking and concentration occurs as the temperature increases (16) and the optimum level of temperature for a comfortable learning environment is 20-21°C (10,17).…”
Section: Introductionmentioning
confidence: 99%